1972
DOI: 10.1071/bi9721073
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur Metabolism and Excretion Studies in Ruminants IX. Sulphur, Nitrogen, and Energy Utilization by Sheep Fed a Sulphur-Deficient and a Sulphate-Supplemented, Roughage-Based Diet

Abstract: Four Merino wethers were each fed a sulphur-deficient, roughage-based ration containing 1'05% nitrogen (79% as urea) and supplying 135 mg sulphur/day. Four other sheep were fed similar amounts of basal ration supplemented with NasS04. This ration supplied 494 mg sulphur/day. Mter 21-day periods the treatment groups were reversed.Supplemental sulphate increased the daily flow of protein nitrogen to the omasum by 2·09 (±0·28) g/day (mean ± S.E.M.) (p<0·001) and changed the nitrogen balance from -2·38 (±0·09) g/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

1976
1976
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 7 publications
1
18
1
Order By: Relevance
“…The addition of sulfur to roughage diets generally has increased voluntary intake Siebert, 1972, 1973;Playne, 1969) digestibility of crude fiber (Bray and Hemsley, 1969;Deif et al ,1970;Hume and Bird, 1970;Kennedy and Siebert, 1972;Starks et al, 1954) and energy utilization (Bird, 1972 (Begg and Freney, 1960). Also, moisture stress depresses the sulfur and crude protein content of forages.…”
Section: Nitrogen Energy and Mineral Supplementationmentioning
confidence: 99%
“…The addition of sulfur to roughage diets generally has increased voluntary intake Siebert, 1972, 1973;Playne, 1969) digestibility of crude fiber (Bray and Hemsley, 1969;Deif et al ,1970;Hume and Bird, 1970;Kennedy and Siebert, 1972;Starks et al, 1954) and energy utilization (Bird, 1972 (Begg and Freney, 1960). Also, moisture stress depresses the sulfur and crude protein content of forages.…”
Section: Nitrogen Energy and Mineral Supplementationmentioning
confidence: 99%
“…The efficiency of incorporation of recycled sulphate into microbial protein was thus low,even when the primary limitation to microbial growth on this same diet appeared to be sulphur deficiency (Bird 1972b), and probably reflected the rapidity of absorption of sulphide from the rumen. For example, Bray's (I 969b ) data indicate that the mean time spent by sulphide molecules in the rumen may be as low as 14-31 min.…”
Section: Discussionmentioning
confidence: 99%
“…The diet was similar to the basal diet of Bird (1972b) and consisted of oat hulls (83 %), starch (6 %), sucrose (6 %), minerals (3 %), and urea (2 %). The mineral mixture was that described by Hume and Bird (1970).…”
Section: Sheep and Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Bird (1972) showed that with S-deficient, urea-oat hulls diets, ruminal degradation of organic matter was limited, compared with S supplemented diets. It is not certain, however, that in the present study S was the primary limiting factor, especially because it was demonstrated with sheep that when the level of digestible energy was sufficient urea supplementation still enhanced microbial growth, even with N to S ratios of up to 60 to 1 (Elliott and Armstrong, 1982).…”
Section: Discussionmentioning
confidence: 99%